2020
DOI: 10.1021/acs.oprd.0c00085
|View full text |Cite
|
Sign up to set email alerts
|

Reductive Amination Bicarbonate Quench: Gas-Evolving Waste Stream Near-Miss Investigation

Abstract: The use of sodium triacetoxyborohydride (STAB) as a mild and effective reagent for the reduction of imines is well characterized in the literature. For reduction products that require a nonacidic workup, but cannot tolerate a strongly basic quenching regime, the reaction mixture is typically quenched with bicarbonate solution in excess to neutralize any remaining active reagent. We recently experienced a near-miss incident in our pilot plant operation, where the drummed, aqueous waste stream from a reductive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…SDSs do not always fully characterize the hazards of a chemical, and it is up to the individual scientists to do the appropriate level of due diligence before work is carried out. Continual sharing of near misses 28 is also critical to ensuring safety in both industry and academia.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…SDSs do not always fully characterize the hazards of a chemical, and it is up to the individual scientists to do the appropriate level of due diligence before work is carried out. Continual sharing of near misses 28 is also critical to ensuring safety in both industry and academia.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…Typical root causes of drum overpressurization are gas generation from chemical reactions, biological activity, radiolysis, and temperature/pressure changes. One near-miss incident associated with drum overpressurization reported in 2020 showed that the drummed, aqueous waste stream from a reductive amination process generated unexpected internal pressure due to slow CO 2 generation, resulting in significant deformation of a mild steel drum during temporary storage . In more severe cases of drum overpressurization, both the top and bottom of the drum will be distended.…”
Section: Introductionmentioning
confidence: 99%
“…One near-miss incident associated with drum overpressurization reported in 2020 showed that the drummed, aqueous waste stream from a reductive amination process generated unexpected internal pressure due to slow CO 2 generation, resulting in significant deformation of a mild steel drum during temporary storage. 7 In more severe cases of drum overpressurization, both the top and bottom of the drum will be distended. In these cases, a safer approach for mitigating the situation is to use a remotely controlled drum punch.…”
Section: Introductionmentioning
confidence: 99%
“…9,11,12 Although these measures can improve the stability of the coupling partner, they are in contrast to the green chemistry principals due to reduced atom efficiency as well as generation of extra organic waste and boron-containing aqueous waste streams. 13 An additional aspect relates to preclinical safety and the high likelihood of boronic acid derivatives to trigger an in silico alert for mutagenicity, which can require the development of challenging and time-consuming analytical control and testing strategies. 14,15 In this context, the substitution of heteroaryl boronic acid derivatives by their corresponding sulfinate salts opens the opportunity to circumvent the above-mentioned concerns and allows access to a complementary cross-coupling strategy.…”
mentioning
confidence: 99%
“…Although these measures can improve the stability of the coupling partner, they are in contrast to the green chemistry principals due to reduced atom efficiency as well as generation of extra organic waste and boron-containing aqueous waste streams . An additional aspect relates to preclinical safety and the high likelihood of boronic acid derivatives to trigger an in silico alert for mutagenicity, which can require the development of challenging and time-consuming analytical control and testing strategies. , …”
mentioning
confidence: 99%